ANALISIS PENGARUH PERDAGANGAN INTRA-REGIONAL DAN EKTRA-REGIONAL ASEAN TERHADAP PERTUMBUHAN EKONOMI NEGARA-NEGARA ASEAN-5 - Baida Soraya (Universitas Negeri Medan, 2013)
Economy growth is one of indicators of people prosperity in a country. ASEAN is a type of economic integration which aim to increase economic growth of member countries. Intra-regional and extra-regional trade is kind of trade agreement which aim to increase the trade rate and economic growth. However, the rate of extra-regional trade in every ASEAN-5 countries is higher than intra-regional trade. The objective of this research is to analyze the factors which effect the economic growth of ASEAN-5 countries during 2007-2011. With random effect model in pooled data processing, the research result described that extra-regional trade of ASEAN, foreign direct investment, inflation, and the population described positive and significant effect to economic growth of every ASEAN-5 countries. Whereas, intra-regional trade of ASEAN effect positive and insignificant to the economic growth of ASEAN-5 countries.